Assessing terrain shifts and infrastructure impact: A dual approach using satellite imagery and UAV data in the Cibedug, Rongga landslide - Hilmi Zaenal Putra Moch; Tohari Adrin; Fakrus Shomim Achmad; Soebowo Eko; Sudrajat Yayat; Amar; Wahyudin; Sarah Dwi (E3S Web of Conferences)
This study investigates the Rongga landslide, located on the southwest-facing slope of the southern mountain range in West Java, Indonesia, which is particularly prone to landslides due to its geological composition and topographical features. The research integrates high-resolution satellite imagery and UAV data to analyse the vertical, horizontal, and rotational displacements caused by the landslide. Vertical displacement was observed at the main crown, right flank, and left flank, with variations ranging from 1.5 to 4 meters. Horizontal movement was quantified across different zones of the landslide, with the upper zone experiencing the greatest displacement of 6.5 meters, and the lower zone showing the least at 3 meters. Rotational movements were significant in the upper and lower zones but were absent in the middle zone. This comprehensive analysis provides valuable insights into the dynamics of the Rongga landslide and lays the groundwork for future mitigation strategies.